Salinas e lo Steri: un nuovo museo per una nuova città (ACME, 2023)
Through the study of two singular unpublished and undated floor plans, light is shed on a unknown page of palermitan museology: the proposal, never implemented, by Antonino Salinas, supported also by Giuseppe Fiorelli and Paolo Boselli, to transfer all the archaeological, medieval and modern art collections between 1887 and 1910 from the spaces of the former convent of the Filippini fathers to the Olivella in the medieval complex of Palazzo Chiaramonte or Steri. The unfortunate choice of post-unification destiny the former convent which houses the Museum of Palermo, the National Exhibition of 1891/1892 and the “taglio” of via Roma, carried out in the early 1900s for the construction of the new major city thoroughfare, are the reasons which pushed the actors of the story to raise the question. Documentary research, which describes the events up to 1932, reveals many of the dynamics and problems relating to the facts such as the possible establishment of a new museum center, a suggestive redeveloped urban area, that there is almost an entire district dedicated to museums. The new exhibition project of the Salinas is in a line of continuity with the well-known idea of the palermitan archaeologist to celebrate the “history of the arts of the whole Sicily” and at the same time anticipates some of the exhibition choices, which will be adopted later by Marconi and Accascina: unique among the contemporary national museums of the peninsula.